Compounded effects on wetland greenhouse gas fluxes from climate change and water management along a saline to freshwater gradient - Cheryl L. Doughty; Qing Ying; Eric Ward; Erin Delaria; Glenn M. Wolfe; Sparkle L. Malone; David E. Reed; Tiffany Troxler; John S. Kominoski; Edward Castañeda-Moya; W. Barclay Shoemaker; David Yannick; et al. (Proceedings of the National Academy of Sciences, 2026)
Saline and freshwater wetlands store large amounts of carbon, which has driven interest in their role as nature-based climate solutions. Because these ecosystems can be both sinks and sources of carbon to the atmosphere as environmental conditions and human influence change, the net climate mitigation potential of wetlands at regional to global scales remains uncertain. We used a data-driven approach to measure ground-based and airborne fluxes to upscale carbon dioxide (CO 2 ) and methane (CH 4 ) fluxes using satellite-based surface reflectances at 500-m resolution across a gradient of saline to freshwater wetlands in Southern Florida, USA. Daily time series of CO 2 and CH 4 fluxes from 2000 to 2024 integrated surface properties related to vegetation productivity, flooding, and disturbance, and captured 80% and 91% of the variability in annual fluxes of CO 2 and CH 4 , respectively. Long-term (23-y) patterns in the fluxes of CH 4 , CO 2 , and their CO 2 -equivalent (CO 2 eq) are represented as Global Warming Potential 100 (GWP100) and were shown to vary spatially with wetland management, revealing higher carbon uptake in mangroves susceptible to hurricane damage and coastal hydrology, and greater carbon emissions in freshwater sawgrass marshes where freshwater hydrology is managed for restoration. Regional net annual CO 2 eq uptake in coastal and freshwater wetlands increased by 18% from −7.0 ± 3.3 MMT CO 2 eq y −1 in ~2003 to −8.4 ± 3.8 MMT CO 2 eq y −1 in ~2020 at an uptake rate of −0.06 ± 0.01 MMT CO 2 eq y −2 . Annually, roughly 43% of CO 2 uptake was offset by CH 4 emissions from all wetlands in the region (from 16% in mangroves to 82% in freshwater marshes).